(3OjhGf CHj aQGS GdMeOGfjs - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3bO cGf HOQ GdJeGe oMrSfG hGdfGS aj MHg ShGA s
(3BNQgG (B:s
(3ef CQLhRI aj GdWQO(B: (3hde fRd SHY djGmd YOOG CSYnO ef QGM aGSXj ef ZOG s
(3Vef eLehY s
(3fSNI KGdKI YJjbIs
(3hQO CjVkG JMJ Qbe (B475s
(3ChbagG GdSdWGf CMeO GdefUhQ GdPgHj Ydi NRGfI GdbQhjjf hPdc HYO Cf cJH YdjgG UjZI GdJMHjS HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs